Quantum illumination networks - Xiaobin Zhao; Zheshen Zhang; Quntao Zhuang (Communications Physics)
Abstract Quantum illumination is an entanglement-based target detection protocol that provides quantum advantages despite entanglement-breaking noise. However, the advantage of traditional quantum illumination protocols is limited to impractical scenarios with low transmitted power and simple target configurations. Here, we address these challenges by introducing a quantum illumination network that leverages a transmitter array and a single receiver antenna. Thanks to multiple transmitters, quantum advantage is achieved with a high total transmitted power. Furthermore, the network resolves complex target configurations involving multiple unknown transmissivity or phase parameters. Despite the interference of different returning signals at the single antenna and photon loss due to multiple-access channels, we develop two types of measurement designs: one based on parametric amplification and the other on correlation-to-displacement conversion. Finally, we generalize the parameter estimation scenario to a general hypothesis testing scenario, where the six-decibel quantum illumination advantage is achieved at a much greater total probing power.